The Cambridge companion to British romanticism and religion - Barbeau, Jeffrey W. (Cambridge companions to topics, 2021)
The Cambridge Companion to British Romanticism and Religion provides the first scholarly survey of the connections between literature, religion, and intellectual life during the British Romantic period (1780s-1832). Part I, 'Historical Developments,' examines diverse religious communities, texts, and figures that shaped British Romantic culture, investigating the influence of Christianity, Judaism, Islam, Hinduism, and atheism on the literature of the times. Part II, 'Literary Forms,' considers British Romanticism and religion through attention to major genres such as poetry, the novel, drama, sermons and lectures, and life writing. Part III, 'Disciplinary Connections,' explores links between religion, literature, and other areas of intellectual life during the period, including philosophy, science, politics, music, and painting.